Przejawy słowiańskiej i skandynawskiej obrzędowości pogrzebowej doby "plemiennej" na cmentarzysku w Myszęcinie na Ziemi Lubuskiej - Pawlak, Paweł (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2018)
The article presents the results of research into an early medieval burnt offering grave field inMyszęcin, Świebodzin county. The field contained pit graves, some of which are reminiscent ofthe Alt Käbelich-type graves popular especially in the north-western part of theWestern Slavic Territory. On the basis of artefacts discovered in the grave pits and on the surface of the grave field, primarily as a result of an analysis of ceramics, the graves can be dated back to the mid-8th and the 9th centuries.